Aspects of fruit growth and rootstock/scion influence on field performance in kiwifruit (Actinidia deliciosa (A. Chev.) C.F. Liang et A.R. Ferguson var. deliciosa) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Horticultural Science at Massey University - Cruz, Castillo Juan Guillermo (Massey University, 1994)
The influence of nine Actinidia deliciosa (A. Chev.) C.F. Liang et A.R. Ferguson var. de!iciosa rootstocks and four 'Hayward' strains on the growth and cropping performance of kiwifruit vines four, five, and six years after grafting was determined. Multivariate analysis of variance on phenotypic data was an effective technique to distinguish main effects of rootstock and scion and the interactions between the two. Canonical Variate Analysis was particularly useful for distinguishing between root systems, 'Hayward' selections and their interaction on the basis of field performance. This statistical technique was highly effective in summarizing the complex relationships of the data and provided a useful method of reducing the dimensionality of the problem. A rootstock effect on plants topworked on root system 4 (male) was characterised by high field performance, as expressed by high floral bud burst and high yield of large size fruit in each of three seasons. Own rooted vines had the highest field performance in one season. Own rooted 'Hayward' B strain had a large trunk diameter and high yield in comparison to the other three own rooted 'Haywards', in two seasons. In contrast, when strain 'B' was topworked across eight root systems the vines produced a low yield of small fruit in two seasons. 'Hayward' A as a scion achieved the best field performance in yield and fruit sizing across eight root systems in two seasons. Root system and scion interactions were characterised by differences in 'Hayward' selection effects on individual root systems, and root system effects on individual 'Hayward' selections. In particular scion performance on root system 9 differed significantly, as did the effect of rootstock on the scion selection 'Hayward' D. Fruit from some vines had a significant increase in percentage of soluble solids and fruit firmness at harvest, and during storage. Scion effects on percentage of soluble solids present at harvest were lost after fifteen weeks of cold storage. Conversely, in some cases, significant interaction between rootstock and scions on that variate were found only after a period of fruit storage. Rapid fruit softening during storage occurred in some rootstock scion combinations, particularly 'Hayward' Con its own roots and three of the eight rootstocks. The effects of early summer partial defoliation on fruit size, return bloom, and carbohydrate content of 'Hayward' kiwifruit vines were studied. An arbitrary distinction was made between shoots arising from the 'replacement cane zone' (RCZ), the wide horizontal area between the T-bar support wires, and the fruiting zone (FZ), comprising all growth arising outside the T-bar support wires. A 75 % defoliation of new shoots in the RCZ significantly reduced mean fruit size 13 and 7 g, in the RCZ and FZ, respectively, and starch content of the shoots as determined in March. The treatments did not significantly alter the root starch content over several dates sampled. The return bloom of the vines was significantly reduced by 50 and 75 % defoliation. Pre-anthesis factors and early fruit growth were important in determining final fruit size. Ovaries from early opening flowers had significantly greater fresh weight than late ovaries. Cell number and cell size in the inner and outer pericarp of the ovary at anthesis were similar for early and late opening flowers but core cell number was significantly higher for ovaries from early flowers. At commercial harvest, the cell number in the outer pericarp of fruit from early flowers was greater than fruit from late flowers. When treated with the synthetic cytokinin CPPU (N-(2-chloro-4-pyridil)-N-phenylurea), fruit from early flowers achieved a larger fruit size than fruit from late flowers. Fruit weight response to the synthetic cytokinin CPPU was enhanced when applied in combination with GA₃ (gibberellic acid) + 2,4-D (2,4-dichlorophenoxyacetic acid) in three seasons. In treated 'Hayward' fruit, the relative thickness of the outer pericarp was increased, and the inner pericarp decreased. Low and high seeded fruit treated with the hormone mixture had mean fresh weights of 102 and 136 g, respectively, compared with 47 and 90 g in untreated fruit. In kiwifruit inner pericarp cultured in vitro there was no callus growth in the absence of hormones, even when seed were present. A mix of 2,4-D + GA₃ + BAP (6-benzylaminopurine) stimulated callus growth. In the presence of 2,4-D + GA₃ , seeds or BAP increased fruit callus growth and reduced the phytotoxicity effect of abscisic acid (ABA). The uptake of ¹⁴C-CPPU and ¹⁴C-CPPU + 2,4-D + GA₃ by 'Hayward' kiwifruit, and the distribution of radioactive label in fruit tissues was examined. After 21 days the recovery of radioactivity was significantly greater from fruit treated with mixture compounds to CPPU alone. At commercial harvest radio-active metabolites of CPPU were on average 6.2 and 4.8 ppb (fresh weight basis) for soluble and insoluble acetone fractions, respectively. Of this activity, 90 % was present on the skin, and 10 % in the flesh.
Appendix for Published Papers not included due to copyright. May be viewed in the print copy held in the library.
Keywords: Kiwifruit; Rootstocks; Growth; Vitality; 300803 Horticultural crop improvement (incl. selection and breeding)